The Paradox of Demand-Supply and Price Dynamics during Covid-19 Pandemic: A Comparative Study on Pharmaceutical, Bakery and Table-Water Companies in Lagos, Nigeria - Edih O. University; Dbright O. Agboro; Irejeh E. Minna (Budapest International Research in Exact Sciences (BirEx) Journal, 2022)
The sudden emergence of Covid'19 pandemic amounts to monumental disruptions in global economic activities due to stringent measures such as lockdown of international and local transport systems and social distancing that were drafted to curtail the surging scourge. It might be a probable cause of the noticeable dramatic dynamics in demand, supply and prices of goods and services. The study examined the paradox of demand-supply and price dynamics during covid'19 pandemic: a comparative study of pharmaceutical, bakery and table water companies in Lagos, Nigeria. The study employed structured questionnaires to generate primary data which were analyzed using chi-square method corroborated by oral interview. A total number of 90 set of questionnaire were distributed to 30 selected companies. Results revealed that there were no price variation in pharmaceutical products, bakery products and table water companies’ products during the first wave. This is because the restriction of movement did not affect essential commodities and international borders were open for pharmaceutical goods as well as other essential products. However, interview report showed that there were moderate increase in demand for bakery and table water companies products with no corresponding rise in prices. It was made possible by active policy directives of the national and state governments that were implemented by monitoring groups. The paper suggests that during global exigencies, the net of essential commodities should be widened and their prices controlled as well as avoid artificial hoarding to meet up with the upsurge in demand which is a necessary outcome during epidemic.